Perceptions of Some Aspects of a Career Guidance and Counselling Program at the Secondary Level - Penner, Wes; McLeod, Heleen; Nichols, Al; Grant, Jacquie (Canadian Journal of Counselling and Psychotherapy, 2012)
The present research project was undertaken to assess the opinions and perceptions of students, parents and community representatives of a number of aspects of a typical secondary school career guidance program. And, secondly, the study was designed to elicit opinionsof the ways in which career guidance could most effectively be improvedand facilitated. The responses to questionnaires and interviews completed by random samples of the three target populations indicated a wide distribution of opinion on certain aspects of the program and a marked consensus on other facets of the same career guidance program. In particular, it was found that there was little relationship between students' career choices and knowledge of the educational training required for the choice, as well as a vast difference between the proportion of parents who positively evaluated the guidance program with respect to academic counselling and the proportion of parents who positively evaluated theguidance program with respect to career counselling. There was, however, marked agreement between parents and community representatives with regard to the nomination of potentially effective methods for the improvement of career guidance programs. Le présent projet de recherche voulut premièrement déterminer les vues et les opinions d'étudiants, de parents et de représentants de bureaux de placement concernant plusieurs aspects d'un programme d'orientation professionnelle à l'école secondaire. En second lieu, cette étude fut menée afin de susciter des opinions chez ces personnes quant aux façonsselon lesquelles l'orientation professionnelle pourrait être le plus efficacement facilitée et améliorée. Les réactions de ces trois groupes de personnes aux entrevues et aux questionnaires administrés au hasard ont indiqué que l'opinion est diverse relativement à quelques aspects du programme et en harmonie relativement à d'autres aspects du mêmeprogramme. Notamment, on a trouvé qu'il y avait peu de rapport entrele carrière choisie par l'étudiant et sa familiarité avec l'éducation etles qualifications requises pour cette profession. De plus, il y avaitune différence notable entre la proportion de parents qui faisaient uneévaluation positive du programme d'orientation en ce qui concerne laconsultation académique, et la proportion de parents qui en faisaient une évaluation positive en ce qui concerne l'orientation professionnelle.Il y avait, cependant, un accord prononcé entre les parents etles représentants de bureaux de placement en ce qui concerne l'identification de méthodes qui pourraient améliorer l'orientation professionnelle.